Proceedings of the Twenty-Fifth Annual Symposium on Computational Geometry 2009
DOI: 10.1145/1542362.1542413
|View full text |Cite
|
Sign up to set email alerts
|

A general approach for cache-oblivious range reporting and approximate range counting

Abstract: We present cache-oblivious solutions to two important variants of range searching: range reporting and approximate range counting. The main contribution of our paper is a general approach for constructing cache-oblivious data structures that provide relative (1 + ε)-approximations for a general class of range counting queries. This class includes three-sided range counting, 3-d dominance counting, and 3-d halfspace range counting. Our technique allows us to obtain data structures that use linear space and answ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 44 publications
(55 reference statements)
0
22
0
Order By: Relevance
“…Combined with counting arguments, this ensured that the point set cannot be represented in linear space while guaranteeing a certain proximity (on disk) of the points reported by each query. The problems we study in this paper allow linear-space or O(N log * N)-space solutions in the I/O model [1,2,8], as well as linear-space cache-oblivious solutions for queries of any fixed output size [3,5,10]. This means the previous techniques are ineffective for our purposes.…”
Section: New Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Combined with counting arguments, this ensured that the point set cannot be represented in linear space while guaranteeing a certain proximity (on disk) of the points reported by each query. The problems we study in this paper allow linear-space or O(N log * N)-space solutions in the I/O model [1,2,8], as well as linear-space cache-oblivious solutions for queries of any fixed output size [3,5,10]. This means the previous techniques are ineffective for our purposes.…”
Section: New Resultsmentioning
confidence: 99%
“…Afshani [1] showed that an optimal query bound can in fact be obtained using linear space, raising the question whether this result can be achieved also in the cache-oblivious model. In [3], we show that the optimal query bound can indeed be achieved by a cache-oblivious data structure, but our data structure uses O(N log N) space.…”
Section: Related Workmentioning
confidence: 97%
See 1 more Smart Citation
“…Since approximate counting is at least as difficult as deciding emptiness, the ultimate goal is to get bounds matching those of emptiness. For example, for approximate 3-D halfspace range counting, Afshani et al [2,3] (improving earlier results [6,24]) obtained linear-space data structures with O(log n) query time. These algorithms can be adapted to solve the related 3-D 3-sided orthogonal range counting problem (i.e., 3-D dominance counting), which includes 2-D 3-sided range counting as a special case.…”
Section: Introductionmentioning
confidence: 90%
“…All computation has to happen on data in internal memory. The transfer of data between internal and external memory happens in blocks of B consecutive data [3,4,7,11] 2-d dominance N log B N + K/B cache-oblivious, [11] 3-d dominance N log N + K internal memory, [1,20] N log B N + K/B I/O model, [1] N log N log B N + K/B cache-oblivious, [3] 3-d halfspace N log N + K internal memory, [2] N log * N log B N + K/B I/O model, [2] N log N log B N + K/B cache-oblivious, [3] Table 1: A summary of related work on three-sided range reporting, 2-d and 3-d dominance reporting, and 3-d halfspace range reporting with the optimal query bound.…”
Section: Introductionmentioning
confidence: 99%